2007
DOI: 10.1080/00016340701332811
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal sacrospinous colpopexy and laparoscopic sacral colpopexy for vaginal vault prolapse

Abstract: This study indicates that VSC and LSC are two equally effective surgical procedures to correct vaginal vault prolapse, but the LSC technique requires a longer operating time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 15 publications
1
32
0
2
Order By: Relevance
“…One cohort study showed similar anterior and apical outcomes, but more posterior wall recurrences after LSC compared to SSLF (17% vs. 0, p < 0.01). (30) In summary, moderate quality data favors mesh sacrocolpopexy over native tissue vaginal apex repairs in providing anatomic success. This is particularly evident for the anterior and apical compartments.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…One cohort study showed similar anterior and apical outcomes, but more posterior wall recurrences after LSC compared to SSLF (17% vs. 0, p < 0.01). (30) In summary, moderate quality data favors mesh sacrocolpopexy over native tissue vaginal apex repairs in providing anatomic success. This is particularly evident for the anterior and apical compartments.…”
Section: Resultsmentioning
confidence: 98%
“…In their retrospective cohort study,(30) Marcickiwicz et al reported more reoperations for recurrent prolapse in those receiving LSC compared to SSLF [15/60 (25%) vs. 4/51 (8%), p=0.02], though seven of the 15 LSC recurrences were early in the learning curve. Finally, Thompson et al reported on all-cause reoperation in their retrospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mais les urologues ne maîtrisant pas, pour la plupart, la voie vaginale pouvaient ainsi offrir à leurs patientes une technique de cure de prolapsus ayant une morbidité moins importante que la promontofixation par laparotomie et une durée moyenne de séjour identique à la voie vaginale [9,10].…”
Section: Situationunclassified
“…Cheret et al [8] en 2001 montraient que la durée moyenne des promontofixations par coelioscopie était de 170 minutes et que cette durée ne diminuait pas significativement entre les 11 premières patientes et les 11 dernières patientes (sur 44 patientes). En 2007, Marcickiewicz et al [10] notaient un temps opératoire deux fois plus long pour la voie coelioscopique (129 minutes) par rapport à la voie vaginale avec un même taux de succès sur le traitement du prolapsus. La longue courbe d'apprentissage et la durée moyenne des interventions sont-ils des arguments suffisants pour que nous ne réalisions pas de coelioscopies dites « complexes » ?…”
Section: Réticences Des Gynécologuesunclassified